The Role of Schools in Transmission of the SARS-CoV-2 Virus: Quasi-Experimental Evidence from Germany - Clara von Bismarck-Osten; Kirill Borusyak; Uta Schönberg (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
This paper considers the role of school closures in the spread of the SARS-CoV-2 virus. To isolate the impact of the closures from other containment measures and identify a causal effect, we exploit variation in the start and end dates of the summer school and fall holiday across the 16 federal states in Germany. Leveraging a difference-in-differences design with staggered adoption, we show that neither the summer closures nor the closures in the fall have had any significant containing effect on the spread of SARS-CoV-2 among children or any spill-over effect on older generations. We also do not find any evidence that the return to school at full capacity after the summer holidays increased infections among children or adults. Instead, we find the number of children infected increased during the last weeks of the summer holiday and decreased in the first weeks after schools reopen, a pattern we attribute to travel returnees and increased testing.
Keywords: I10; I18; I28; 330; Covid Economics; School Closures; Public Health